Pharmacology - Pharmacology (Whalen); Whalen, Karen; Feild, Carinda; Radhakrishnan, Rajan (Philadelphia : Wolters Kluwer, 2019)
"Lippincott Illustrated Reviews: Pharmacology, Seventh Edition, is t he updated, enhanced version of the student-favorite resource for essen tials of medical pharmacology. The first-and-best resource, the Lippinc ott Illustrated Reviews series features clear, effective writing and hu ndreds of illustrations for ideal rapid review and the assimilation of complex information. Clear, sequential images present mechanisms of act ion and focus on showing rather than telling students how drugs work. N early 600 annotated, full-color illustrations visually explain complex processes! Outline format ideal for concise review and foundational lea rning"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pharmacology